Simon and the bear : a Hanukkah tale - Kimmel, Eric A.; Trueman, Matthew (Los Angeles : Disney/Hyperion Books, 2014)
Stranded on an iceberg on his way to America, Simon remembers his mother's parting words and lights the first candle on his menorah while praying for a miracle, which soon arrives in the form of a friendly polar bear.
School Library Journal, October 2014
Publisher's Weekly, September 2014
Kirkus Starred, September 2014
New York Times, December 2014
Horn Book, November 2014
3.0.
Keywords: Miracles -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Shipwrecks -- Fiction; Hanukkah -- Fiction; Polar bears -- Fiction; Bears -- Fiction; Jews -- Fiction; Picture books for children